Ligand Migration in Human Indoleamine-2,3 Dioxygenase - Nienhaus, Karin (IUBMB Life, 2011)
Human indoleamine 2,3-dioxygenase (hIDO), a monomeric heme enzyme, catalyzes the oxidative degradation of L-tryptophan (L-Trp) and other indoleamine derivatives. Its activity follows typical Michaelis–Menten behavior only for L-Trp concentrations up to 50 µM; a further increase in the concentration of L-Trp causes a decrease in the activity. This substrate inhibition of hIDO is a result of the binding of a second L-Trp molecule in an inhibitory substrate binding site of the enzyme. The molecular details of the reaction and the inhibition are not yet known. In the following, we summarize the present knowledge about this heme enzyme.